Pre-service Teacher Strategies in Empowering Ethics in Using AI in Classroom - Ade Rahma Romadhona Arroyan; Daniel Ari Widhiatama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to examine the strategies used by pre-service teachers to promote the ethical use of Artificial Intelligence (AI) in the classroom and the challenges they face in the teaching process. This study uses a descriptive qualitative approach, and the data were collected through semi-structured interviews with five pre-service teachers. The data were analyzed using Reflexive Thematic Analysis, following Braun and Clarke’s framework and guided by the perspectives of AI-TPACK and Teacher Agency frameworks. The results show that pre-service teachers apply four main teaching strategies to encourage the ethical use of AI in the classroom, including scaffolding strategies, modelling strategies, assessment design, and critical literacy. These strategies help students use AI as a learning support tool rather than replacing their own thinking. However, in implementing the strategies, pre-service teachers face four main challenges, such as knowledge gaps, institutional barriers, student resistance, and unclear boundaries between acceptable language support and AI-generated content. Overall, the findings highlight the need for better preparation in AI literacy and AI ethics in teacher education programs and emphasize the importance of integrating ethical AI pedagogy into pre-service teacher training.